Relações entre valores, sentido da vida e bem-estar subjetivo em membros de novas comunidades católicas - Aguiar, Andrei Alves de (2011)
The religiosity in general is still a core to the Brazilian culture, influencing their attitudes and behaviors.Even considering the importance of studying minority groups as important objects of research, the growth of some organizations, such as the "New Life and Alliance Catholic Communities", shows a shift in the religious experience of the contemporary world. Although there are many studies about human values, meaning of life and well-being, there are very few studies about the relationship of these constructs with the members of some religious institutions. The lack of studies in this area shows how significantly important is the research and analysis of this new social group, through the scientific view of what values are prevalent in those who participate of such institutions, and also to give attention to the level of well-being and sense of life of the people who live there. This study aimed to investigate the existential and value correlates of the participants of the New Catholic Communities present in the area of João Pessoa city. To this end, counted with the participation of 147 members of new communities in a convenience sample (not random). The ages of the participants ranged between 18 and 65 years (M = 29.31, DP = 10.89), most of the participants having completed high school (38.8%), most singles (60.5%) and women (63.9%). All were asked to fill the PIL Test scales (Purpose in Life), General Health Questionnaire 12, QVB and Basic Values Questionnaire, as well as the sociodemographic questionnaire. It was observed that the most important values on those organizations are the religiosity and obedience, and that the subfunctions were much more normative and interactive. It was also observed that members of the group "life community" give more importance to the value of obedience, when compared to members of the "alliance community" and that the men give more importance to the subfunction achievement than women. Depression was positively correlated with the subfunction experimentation, the anxiety was positively correlated with the subfunction existence, depression and anxiety where also positively correlated with the existential emptiness. On the other hand, the existential emptiness was negatively correlated with the fact that the member feel important to his community and the condition of having partner of the same community, which represents protection factors of subjective well-being . The results were analyzed in the light of human values and the theoretical perspective of Viktor Frankl.